Digital Disruption at Field Level: Tipping Point Experiments from Rice Sector - Shaik N. Meera, S. Arun Kumar, Praveen Rapakaand S.R. Voleti (Indian Journal of Extension Education, 2023)
Future Extension and Advisory Services (EAS) across the globe need to innovate and strategize the use ofdisruptive technologies such as mobile/cloud computing, Internet of Things, big data analytics, locationbasedsocial networks, blockchain technologies etc. Use of digital technologies in rural advisories has beendocumented well in past two decades, but there has been no cross learning between organizations, extensionorganizations, value chain stakeholders and farmers. The paper presents results from a series of tippingpoint pilot experiements conducted in Indian rice industry and probable scalingup options. In theseexperiments, value chain players and farmers were involved with randomised control trials and primarysurveys. Randomised Control Trials (RCTs) were conducted in Southern provinces in India involving farmersand data were analyzed with one way ANOVA. For value chain players, a series of survey based experimentsare conducted. The yield gains in T1 (Digital extension interventions and social media) were significantlyhigher compared to T2, T3 and Control (.034, .041, .002) at 5 per cent level of significance. Similar analyticsare done in entire supply chain management in Indian rice industry that helps shaping future extensionadvisory systems specific to Asian & African rice industry. These experiments suggest that rice industrycan realize disruptive innovations in extension delivery with the help of big data analytics for mappinginputs supply and marketing, location based services for resource tracking & dynamic distribution, virtualpooling for higher market prices, weather fore-warning, proximity-based notification (push or pull) ofadvisories and targeted advertising.